Beyond documentation: an analytical approach towards the future of museums as information centres - Chaterera, Forget (Midlands State University, 2014)
In view of the records preservation status in Zimbabwe’s National Museums, this study tries to ascertain the future of museums as information centres. Using the records life cycle principle and the continuum model which state that documents should be properly managed from the time they are created until their ultimate disposal, this study examined the preservation strategies employed by Zimbabwe’s National Museums to ensure their records survive into the future. For the museum’s purpose in life to be justified and meaningful, records that are generated as a result of the museum's programmes and activities must be regarded as corporate assets, whose preservation should be given due consideration. Using the survey research design, the study employed interviews; questionnaires, observations and the social media to collect data from the informants of the study. An overview of the significant findings of the study reflects that museum records management issues are not yet an appreciated phenomenon in Zimbabwe’s National Museums. That was evidenced by the lack of knowledge and practice on basic records management activities such as the availability of a records management policy, records procedures manual, conducting records surveys, creating retention and disposal schedules. Objects are the raison d’etre of museums and this renders object records as mission critical, to the extent that museums cannot function without them. The study established that museum practitioners in Zimbabwe’s National Museums focus absolutely on objects and object related records. The value of records related to other museum functions or those that document wider administrative and business activities is largely overlooked. These records include documentation concerning building maintenance, development, finance, staff, exhibitions and projects. To that effect, museum practitioners are encouraged to consider managing museum records as part of their key duties.